Impact of Personality Traits on The Investor Sentiment - Taufik Nur Hidayah; Lisa Kustina (International Journal of Business Economics (IJBE), 2020)
In making investment decisions on the Indonesian Stock Exchange, this study evaluates the relationship between personality traits and individual investor activity bias.  This research uses a questionnaire obtained from Indonesia's 205 individual investors. Modelling of structural equations (SEM) is used to analyse the impact of personality characteristics on component behaviour bias. This finding indicates that the traits of neuroticism, extraversion, and openness are strongly related to the different biased behaviours of individual investors on the Indonesian Stock Exchange. This analysis offers evidence that a relationship exists.